THE EFFECT OF STUDENT EXPERIENCE AND PERCEIVED VALUE ON STUDENT SATISFACTION AT XYZ COLLEGE MEDAN - Sjukun, Sjukun; Goh, Thomas Sumarsan; Margery, Errie (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This research was conducted at XYZ College Medan. The purpose of this research was to determine and analyze the effect of Student Experience and Perceived Value on Student Satisfaction. The population in this research was all students of XYZ College Medan and total sample was 85 people. The sampling technique used was purposive sampling. Data collection technique was conducted by distributing questionnaires and documentary studies. Data analysis was done using PLS-SEM (Partial Least Square - Structural Equation Modeling). The finding of this research showed that simultaneously, Student Experience and Perceived Value had a significant effect on Student Satisfaction at XYZ College Medan with a coefficient of determination of 0.609, which means that the the contribution of the Student Experience and Perceived Value variables together on Student Satisfaction was 60.9%, while 39.1% was influenced by variables outside of this reseach. Partially, Student Experience had a positive yet statistically insignificant impact on Student Satisfaction at XYZ Medan. Meanwhile, Perceived Value shows a positive and statistically significant effect on Student Satisfaction at XYZ College Medan.